2006
DOI: 10.1055/s-2006-944545
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Cushing’s Syndrome Have Increased Intimal Media Thickness at Different Vascular Levels: Comparison with a Population Matched for Similar Cardiovascular Risk Factors

Abstract: Cushing's syndrome (CS) is associated with high cardiovascular risk. The aim of this study was to analyze intimal media thickness (IMT) in patients with CS and compare them with subjects matched for similar conventional and independent cardiovascular risk factors. Twenty eight patients with CS (mean age: 40.7 +/- 2.5 y) and 28 subjects (mean age: 41.1 +/- 14 y) matched for sex, age, smoking habit, body mass index, blood pressure levels, glucose and lipid metabolism were evaluated. IMT was measured at right and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 22 publications
2
41
0
3
Order By: Relevance
“…The results of these studies also suggested that beyond a direct effect of glucocorticoid excess on the vascular system, metabolic syndrome may play a pivotal role in carotid atherosclerosis associated with CS. Similar findings were reported also by others [18].…”
Section: Discussionsupporting
confidence: 93%
“…The results of these studies also suggested that beyond a direct effect of glucocorticoid excess on the vascular system, metabolic syndrome may play a pivotal role in carotid atherosclerosis associated with CS. Similar findings were reported also by others [18].…”
Section: Discussionsupporting
confidence: 93%
“…Atherosclerotic plaques are more prevalent in CD patients than in the control population even after long-term remission and correlation with insulin resistance and central adiposity (1,173). IMT correlated with waist-hip-ratio and fasting glucose, but no correlation was found with the cortisol levels (173).…”
Section: European Journal Of Endocrinologymentioning
confidence: 91%
“…In these patients, the carotid vascular damage was significantly and independently correlated with the degree of central adiposity and insulin resistance, demonstrating that these factors mainly contribute to the persistence of vascular damage in patients’ cure of CD. In a different study, an IMT significantly higher than in a population matched for cardiovascular risk factors, such as smoking habit, body mass index, blood pressure, glucose and lipid levels, was described in multiple vascular districts [9]. CS has also been found to be associated with a functional alteration of the vascular system.…”
Section: Vascular Abnormalitiesmentioning
confidence: 99%